Epidemiology of SARS-CoV-2 during the first three waves in Scotland: a national record linkage study. Issue 1 (8th November 2022) - Leslie, Kirstin; Findlay, Beth; Ryan, Theresa; Green, Leonardo I; Harvey, Ciaran; Whettlock, Alice E; Bishop, Jen; Ponce Hardy, Vicki; Went, April; Wallace, Lesley; McLeod, Allan; Weir, Amanda; et al.
Abstract : Background: The early COVID-19 pandemic in Scotland—defined as the era before widespread access to vaccination and monoclonal antibody treatment—can be characterised into three distinct waves: March–July 2020, July 2020–April 2021 and May–August 2021. Each wave was met with various societal restrictions in an effort to reduce disease transmission and associated morbidity and mortality. Understanding the epidemiology of infections during these waves can provide valuable insights into future pandemic planning. Methods: Scottish RT-PCR testing data reported up until 8 August 2021, the day prior to most restrictions being lifted in Scotland, were included. Demographic characteristics including age, sex and social deprivation associated with transmission, morbidity and mortality were compared across waves. A case–control analysis for each wave was then modelled to further compare risk factors associated with death over time. Results: Of the 349 904 reported cases, there were 18 099, 197 251 and 134 554 in waves 1, 2 and 3, respectively. Hospitalisations, intensive care unit admissions and deaths appeared highest in wave 2, though risk factors associated with COVID-19 death remained similar across the waves. Higher deprivation and certain comorbidities were associated with higher deaths in all waves. Conclusions: Despite the higher number of cases reported in waves 2 and 3, case fatality rates were lower: likely a combination of improved detection of infections in younger age groups, introduction of social measures and vaccination. Higher social deprivation and comorbidities resulted in higher deaths for all waves.